2016
DOI: 10.1017/s0021932016000523
|View full text |Cite
|
Sign up to set email alerts
|

Sports Preference and Digit Ratio (2d:4d) Among Female Students in Wrocław, Poland

Abstract: Humans exhibit sex differences in competitiveness, sensation seeking and risk-taking attitude, which are required in sports. These attributes are often linked to prenatal testosterone (PT) exposure. The second-to-fourth digit length ratio (2D:4D) is an indicator of PT exposure. A lower 2D:4D indicates higher PT exposure and vice versa. Males generally have a lower 2D:4D than females. Sensation- and/or thrill-seeking behaviours have also been found to be negatively associated with 2D:4D. Boxing and judo are con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 57 publications
2
25
0
3
Order By: Relevance
“…Kociuba et al (2016) found that in female participants, the judo/boxing group had significantly lower digit ratio than the aerobics group. This suggests that voluntary choice of participation in a sport discipline by women could be linked to the organizational effect of intrauterine testosterone exposure during prenatal growth (Kociuba et al, 2016). …”
Section: Digit Ratio and Preference For High-risk Sportsmentioning
confidence: 88%
“…Kociuba et al (2016) found that in female participants, the judo/boxing group had significantly lower digit ratio than the aerobics group. This suggests that voluntary choice of participation in a sport discipline by women could be linked to the organizational effect of intrauterine testosterone exposure during prenatal growth (Kociuba et al, 2016). …”
Section: Digit Ratio and Preference For High-risk Sportsmentioning
confidence: 88%
“…Association of higher 2D:4D with a dislike or aversion for higher risk was also found even within one sex, as both men and women with lower 2D:4D, compared to their same sex counterparts, chose relatively riskier options (Garbarino et al 2011). Voluntary participation in relatively high risk sports was also associated with lower 2D:4D in polish females independent of their physical ability (Kociuba et al 2017). Therefore the linkage of higher risk taking and lower risk aversion with lower level of PT could also be a plausible explanation for the association of low 2D:4D with the selection or choice of uniformed course in the present study.…”
Section: Discussionmentioning
confidence: 73%
“…A lower 2D:4D among women was also associated with typically male dominated jobs in wide varieties of occupations (Manning et al 2010). Choice of participation in individual-, rather than in group sports among Polish men (Koziel et al 2016), and opting for a specific type of sport among Polish women, were associated with low 2D:4D (Kociuba et al 2017). Although it was argued that the decision to venture in a highly competitive environment was not significantly correlated with 2D:4D (Apicella et al 2011), there was strong evidence of a negative association of 2D:4D with self-reported competitiveness (Bönte et al 2017).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The value of the quotient of finger lengths is determined at the end of the third month of embryonic development, mainly under the influence of prenatal testosterone (PT) and remains unchanged throughout all phases of human ontogenesis (Phelps 1952;Garn et al 1975;Manning et al 1998;Manning et al 2007). On average, in men, finger 4 is longer than the other, i.e., the 2 nd and 4 th fingers length quotient is lower compared to women whose second finger is longer and the quotient approaches 1.00 (Galis et al 2010;Manning et al 2010;Kociuba et al 2017).…”
Section: Introductionmentioning
confidence: 99%